2022
DOI: 10.1186/s13223-022-00645-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of airway smooth muscle cell phenotypes in airway tone and obstruction in guinea pig asthma model

Abstract: Background Airway obstruction (AO) in asthma is driven by airway smooth muscle (ASM) contraction. AO can be induced extrinsically by direct stimulation of ASM with contractile agonists as histamine, or by indirect provocation with antigens as ovalbumin, while the airway tone is dependent on intrinsic mechanisms. The association of the ASM phenotypes involved in different types of AO and airway tone in guinea pigs was evaluated. Methods Guinea pigs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In this study, however, we found that high stretch modulated intracellular levels of cAMP/ATP via miRNA-mRNA, particularly miR-370-5p-PDE4D/AK7 interactions. In addition, we found that miR-370-5p did impact cell stiffness, but not the cell stiffness reduction induced by β-agonist, suggesting that high stretch through miR-370-5p-PDE4D interaction is a mechanical modulator of bronchial airway tone [62] In addition to the modulation of airway tone through contraction/relaxation, ASMCs also modulate airway inflammation by secreting or expressing a wide array of immunomodulatory mediators in response to extracellular stimuli such as high stretch [63]. For example, mechanical stress can induce more pro-inflammatory mediators including IL-1β, IL-8, IL-6, and TNF-α in the distal air spaces of the lung [64].…”
Section: Discussionmentioning
confidence: 78%
“…In this study, however, we found that high stretch modulated intracellular levels of cAMP/ATP via miRNA-mRNA, particularly miR-370-5p-PDE4D/AK7 interactions. In addition, we found that miR-370-5p did impact cell stiffness, but not the cell stiffness reduction induced by β-agonist, suggesting that high stretch through miR-370-5p-PDE4D interaction is a mechanical modulator of bronchial airway tone [62] In addition to the modulation of airway tone through contraction/relaxation, ASMCs also modulate airway inflammation by secreting or expressing a wide array of immunomodulatory mediators in response to extracellular stimuli such as high stretch [63]. For example, mechanical stress can induce more pro-inflammatory mediators including IL-1β, IL-8, IL-6, and TNF-α in the distal air spaces of the lung [64].…”
Section: Discussionmentioning
confidence: 78%
“…Conversely, Qaisar et al. ( 43 ) also reported reduced SERCA expressions in asthma and, in a guinea pig model of asthma, reduced SERCA2b expression in airway smooth muscle cells was recently reported to correlate with intrinsic airway baseline tone ( 44 ). The proinflammatory cytokines, TNFα and IL-13, which are heavily implicated in asthma severity, were shown to decrease SERCA2 expressions in human airway smooth muscle cells ( 23 ).…”
Section: Discussionmentioning
confidence: 99%